A Conceptual Study To Evaluate The Effect Of Virechana Karma, Raktamokshan, And Shaman Aushadha In The Management Of Ekakushtha w.s.r To Psoriasis - Sharma, Himanshu; Singh, Pushpinder; Sood, Rajesh Kumar (International Research Journal of Ayurveda & Yoga, 2021)
Introduction-In Ayurveda all the skin diseases has been discussed under the broad term “Kushtha”. It can be classified into Mahakushtha (major skin diseases) and Kshudrakushtha (minor skin diseases). Ekakushtha is one among the Kshudra Kushtha presenting clinical features – Aswedanam (loss of sweating), Mahavastu (larger area of involvement), Matsya Shaklopamam (scaling)1. Ekakushtha can be correlated with psoriasis on the basis of similarity in etiopathogenesis & symptomatology. Psoriasis is a chronic autoimmune, frequently recurring disease that vary in severity from the merely annoying to life threatening. Although no treatment can completely cure this disease. Acharya has highlighted the role of Panchkarma therapy by stating that the disease treated by Shodhan (Purification treatment) will never recur whereas the treatment with shaman therapy may recur in due course of time. This research work was conducted with the aim to establish an effective therapy under Panchkarma Chikitsa for the management of disease. Method: In this trial 10 patients of Ekakushtha (Psoriasis) were selected from the O.P.D of Panchkarma Dept. RGGPGAC Ayurvedic college & hospital, Paprola, Distt-Kangra H.P. Virechana, Raktmokshana followed by Shaman Aushadha were chosen for the study. Results: The therapy used in this clinical study were found significantly effective in all symptoms of the disease, which were taken for the study. Discussion: Ekakushtha (Psoriasis) is a Kshudrakustha (minor skin diseases), which have Vata Kapha Dosha dominancy. Single dosha cannot cause Kushtha (skin diseases)., we can say it is a Tridoshaja Vyadhi. Acharya indicates Shodhana Chikitsa (Purification) in Bahu Doshaja state of Kustha 2. As per our observation, Virechana (Purgation) and Raktmokshana (bloodletting) followed by Shaman Aushadha (Pacification treatment) are best line of treatment in Ekakushtha (Psoriasis).